Front floor natural gas vehicle platform - Sahari, Barkawi (2009)
A design method for the mounting of gas tanks underneath the front seats on the front platform of natural gas vehicle is provided wherein the gas tanks compartment has a protective shell with reinforcement on the upper half and is held in place from bottom using means of snug fit component.